Theoretical Description of Adsorption from Binary Liquid Non-Electrolyte Solutions with Unlimited Component Miscibility on to Microporous Solids - Dorota Ziółkowska (Adsorption Science & Technology)
The ‘solution’ analogues of four single-gas adsorption isotherms [i.e. the Langmuir-Freundlich (LF), the generalized Langmuir (GL), the Toth (T) and the LF-GL equations] were examined. The derived expressions were applied to the description of the experimental adsorption data relating to the sorption of a binary liquid solution containing components of unlimited miscibility on to microporous solids. Optimization of the equation parameters, as well as a comparison of the results obtained with those determined earlier for sorption in systems where the components were of limited miscibility, was undertaken.